Two-port Network Transfer Function for Power Line Topology Modeling - Mlynek, Petr; Misurec, Jiri; Koutny, Martin; Silhavy, Pavel (Společnost pro radioelektronické inženýrství, 2012)
This paper deals with modeling of power line communication. A two-port network model is theoretically described and compared with measurement. A substantial part is focused on the mathematical description of distri¬bution network using the method, which uses chain pa¬rameter matrices describing the relation between input and output voltage and current of the two-port network. This method is used for modeling sample power line topology. Furthermore, taps length and taps impedance influence on the transfer functions for different topology are examined.
Keywords: Power line communication; two-port network; distribution network topology; transfer function.